Proceedings of the ACM Symposium on Virtual Reality Software and Technology 2001
DOI: 10.1145/505008.505028
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic video system with embedded high spatial resolution images using two channels for transmission

Abstract: Teleoperation requires both wide vision to recognize a whole workspace and fine vision to recognize the precise structure of objects which an operator wants to see. In order to achieve high operational efficiency in teleoperation, we have developed the Q stereoscopic video system which is constructed of four sets of video cameras and monitors. It requires four video channels to transmit video signals. However, four channels are not always available for a video system because of the limitation of the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The second category is the algorithmic approach in which foveation techniques are applied primarily to image processing [2,7], video encoding [6,8], and graphics rendering [9 -11] to achieve real-time video communication through low-bandwidth networks and to save data transmission bandwidth and processing resources. For instance, Geisler and Perry demonstrated a three times greater compression ratio in multiresolution images͞videos [8]; Ienaga et al described a stereoscopic video transmission system with embedded high-resolution fovea images to accelerate the image processing and to reduce the bandwidth requirement [2]; several researchers applied perceptually driven foveation treatments to 3D graphics rendering such a levelof-detail management and polygon reduction in 3D models based on the view eccentricity [9 -11]. Murphy and Duchowski demonstrated that the rendering speed can be significantly accelerated by only rendering high levels of detail of a 3D scene around a user's gaze direction in virtual environments [10]; Luebeke et al demonstrated that 2-6 times fewer polygons can produce the similar rendering effect in perceived model resolution [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The second category is the algorithmic approach in which foveation techniques are applied primarily to image processing [2,7], video encoding [6,8], and graphics rendering [9 -11] to achieve real-time video communication through low-bandwidth networks and to save data transmission bandwidth and processing resources. For instance, Geisler and Perry demonstrated a three times greater compression ratio in multiresolution images͞videos [8]; Ienaga et al described a stereoscopic video transmission system with embedded high-resolution fovea images to accelerate the image processing and to reduce the bandwidth requirement [2]; several researchers applied perceptually driven foveation treatments to 3D graphics rendering such a levelof-detail management and polygon reduction in 3D models based on the view eccentricity [9 -11]. Murphy and Duchowski demonstrated that the rendering speed can be significantly accelerated by only rendering high levels of detail of a 3D scene around a user's gaze direction in virtual environments [10]; Luebeke et al demonstrated that 2-6 times fewer polygons can produce the similar rendering effect in perceived model resolution [11].…”
Section: Related Workmentioning
confidence: 99%
“…Real-time acquisition of high-resolution, wide field of view (FOV), and high dynamic range (HDR) images is essential for many vision-based applications, ranging from the macroscale imaging in surveillance [1], teleconferencing [2], and robot navigation [3], to micrometer or submicrometer-scale imaging in biomedical imaging [4] and vision-guided microfabrication [5]. Although detector technologies have improved dramatically over the past decades, many imaging systems are limited by their performances on FOV, resolution, speed, and dynamic range.…”
Section: Introductionmentioning
confidence: 99%
“…These means, by making tradeoffs between the viewer's primary and peripheral regions of interest, have been used for image processing, video coding [3] and stereoscopic displays [4] to accelerate the image processing and to reduce the bandwidth requirement.…”
Section: Foveated Imaging Systemmentioning
confidence: 99%